(untitled) (Research, Society and Development, 2020)
The occupational nurse significantly attributes to the hospital the development of actions for safety measures, detection and minimization of occupational risks according to the activity performed and the biological injuries to which nursing professionals are exposed, with the objective to improve working conditions. This is a bibliographic research with a qualitative approach, with the objective of describing the work nurse’s work to reduce biological risk in the hospital environment. After the association of all descriptors, 151 articles were found, 138 were excluded and 13 were selected. After the reflective reading, four categories emerged: Main biological adverse events; The Labor Nurse in the prevention of occupational risks. Among the risks to which workers are exposed, hospital infection, the potential transmission of Acquired Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV) and Hepatitis C (HCV), in addition to other harmful occurrences, stand out worker’s health. The role of the work nurse has undergone transformations and evolutions, being today considered a professional of extreme importance for any organization, as through his guidance and attention, accidents and occupational diseases are prevented and the health promotion of workers is also prevented workers. It is concluded that the nurse has training focused on management in addition to being able to perform procedures of lesser and greater complexity as well as prescribing actions, adopting universal precautionary measures for biosafety. Its performance includes strategic planning, which facilitates the development of occupational accidents research and, consequently, their prevention.